COMPARISON OF ALVARADO SCORE AND RIPASA SCORE IN THE ACCURATE DIAGNOSIS OF ACUTE APPENDICITIS IN COMBINED MILITARY HOSPITAL RAWALPINDI: Scoring systems in acute appendicitis - Majid, Muhammad; Maqsood, Rasikh; Ali, Muhammad; Malhi, Muhammad Ayub Ashraf; Hussain, Zaki; Abbasi, Muhammad Hanif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the diagnostic accuracy of Alvarado score and the RIPASA score for acute appendicitis using histopathology as a gold standard.Study Design: Cross sectional validation study.Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2018.Methodology: A total number of 270 patients were included in the study presenting with pain right iliac fossa to the Accident and Emergency department. Surgeons and Seniors Residents in Surgery on call in the Accident and Emergency Department. Combined Military Hospital, Rawalpindi, scored the patients with suspicion of acute appendicitis with Alvarado Score and RIPASA score simultaneously. After appendectomy of these patients, the removed appendix was sent for histopathology to confirm whether it was normal or inflamed. A 2x2 table was used for calculating sensitivity, specificity and diagnostic accuracy of the RIPASA score and Alvarado Score. The two scoring systems were then compared for diagnostic accuracy.Results: In our study, the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of RIPASA score and Alvarado score for diagnosing acute appendicitis were 92.1%, 62.1%, 95.2%, 48.6%, 88.9% and 72.6%, 68.9%, 95.1%, 23.2%, 72.2% respectively.Conclusion: The diagnostic accuracy of RIPASA score was more than that of Alvarado score in diagnosing acute appendicitis.